Do State Holding Companies Facilitate Private Participation in the Water Sector? Evidence from Cote d'Ivoire, the Gambia, Guinea, and Senegal - Kerf, Michel (World Bank, Washington, DC, 2014)
When the Gambia, Guinea, and Senegal decided to involve the private sector in the provision of water services, they also established state holding companies - state-owned entities with exclusive or partial responsibilities for: a) owning infrastructure assets; b) planning and financing investments (replacing assets and expanding networks); c) regulating the activities of the private sector; and d) promoting public acceptance of private participation in the sector. In Cote d'Ivoire, by contrast, when private participation was introduced (in 1960), no state holding company was established. To determine whether state holding companies help private participation in the water sector succeed, the author reviews the four functions these entities are expected to perform in the Gambia, Guinea, and Senegal. In light of experience in all four countries, he examines whether, and under what circumstances, state holding companies might be the entities best suited for carrying out such functions. He concludes that creating a state holding company is often not the best solution. A state holding company might be better suited than other entities for planning and financing investments when (and only when): a) investment responsibilities cannot be transferred to the private operator; b) tariffs are insufficient, at least for a time, to cover investment needs, so it is crucial that a public entity has access to other sources of finance; and c) the holding company's financial strength and accountability, or its incentives and ability to promote the gradual adoption of cost-covering tariffs, are superior to those of a ministerial department. When one or more of these conditions are not met, the main investment responsibilities should be transferred to the private operator or, if that is not possible, left to the government itself. The other three functions should not, as a general rule, be performed by a state holding company.